Genetic characterization of Lassa virus strains isolated from 2012 to 2016 in southeastern Nigeria. - Olamide K Oloniniyi; Uche S Unigwe; Sayaka Okada; Mayuko Kimura; Shota Koyano; Yukiko Miyazaki; Michael O Iroezindu; Nnenna A Ajayi; Chinedu M Chukwubike; Nneka M Chika-Igwenyi; Anne C Ndu; Damian U Nwidi; et al. (Public Library of Science (PLoS), 2018)
Lassa virus (LASV) is endemic in parts of West Africa where it causes Lassa fever (LF), a viral hemorrhagic fever with frequent fatal outcomes. The diverse LASV strains are grouped into six major lineages based on the geographical location of the isolated strains. In this study, we have focused on the lineage II strains from southern Nigeria. We determined the viral sequences from positive cases of LF reported at tertiary hospitals in Ebonyi and Enugu between 2012 and 2016. Reverse transcription-polymerase chain reaction (RT-PCR) showed that 29 out of 123 suspected cases were positive for the virus among which 11 viral gene sequences were determined. Phylogenetic analysis of the complete coding sequences of the four viral proteins revealed that lineage II strains are broadly divided into two genetic clades that diverged from a common ancestor 195 years ago. One clade, consisting of strains from Ebonyi and Enugu, was more conserved than the other from Irrua, although the four viral proteins were evolving at similar rates in both clades. These results suggested that the viruses of these clades have been distinctively evolving in geographically separate parts of southern Nigeria. Furthermore, the epidemiological data of the 2014 outbreak highlighted the role of human-to-human transmission in this outbreak, which was supported by phylogenetic analysis showing that 13 of the 16 sequences clustered together. These results provide new insights into the evolution of LASV in southern Nigeria and have important implications for vaccine development, diagnostic assay design, and LF outbreak management.